RescueNet: An unpaired GAN for brain tumor segmentation. (January 2020) - Nema, Shubhangi; Dudhane, Akshay; Murala, Subrahmanyam; Naidu, Srivatsava
Highlights: A novel network architecture RescueNet is proposed for brain tumor segmentation. An unpaired GAN based training approach is proposed to train the RescueNet. Scale-invariant post-processing algorithm is proposed to enhance the accuracy. Performance of the proposed network is tested on BraTS-2015 and BraTS-2017 dataset. Abstract: Even with proper acquisition of brain tumor images, the accurate and reliable segmentation of tumors in brain is a complicated job. Automatic segmentation become possible with development of deep learning algorithms that brings plethora of solutions in this research prospect. In this paper, we designed a network architecture named as residual cyclic unpaired encoder-decoder network (RescueNet) using residual and mirroring principles. RescueNet uses unpaired adversarial training to segment the whole tumor followed by core and enhance regions in a brain MRI scan. The problem in automatic brain tumor analysis is preparing large scale labeled data for training of deep networks which is a time consuming and tedious task. To eliminate this need of paired data we used unpaired training approach to train the proposed network. Performance evaluation parameters are taken as DICE and Sensitivity measure. The experimental results are tested on BraTS 2015 and BraTS 2017 [1] dataset and the result outperforms the existing methods for brain tumor segmentation. The combination of domain-specific segmentation methods and general-purpose adversarial learning loomed to leverage huge advantages for medical imaging applications and can improve the ability of automated algorithms to assist radiologists.